Strain engineering of microfabricated diamond and its applications - Wenjun Liang; Limin Yang; Jiaqi Zhu; Yiling Lian; Yang Lu (APL Materials, 2025)
Diamond is considered the ultimate semiconductor material due to its excellent physical and electrical properties, such as ultrahigh thermal conductivity, ultrawide bandgap, and superhigh carrier mobility. After ultralarge deformation experimentally conducted on diamond in 2018 and 2021, strain engineering is a highly appealing candidate for tuning these properties of diamond, opening up potential applications in microelectronics and quantum technologies. In this review, we briefly review the implementation of strain engineering on diamond, including introducing dynamic strain by nanomechanical tests and maintaining static strain by various methods. We also provide a brief overview of the strain-induced property changes and the specific applications of the strained diamond.